Organizational Stress as Threat to Reputation: Effects on Anxiety at Work and at Home - Doby, Victoria Jean; Caplan, Robert D. (Academy of Management Journal, 1995)
This study's premise is that job stressors that threaten an employee's reputation with his or her supervisor are particularly likely to generate anxiety symptoms that carry over from work to home. Thirty-six raters, primarily working accountants, identified job stressors as high or low on threat to reputation. Independently, 102 accountants rated their own exposure to these stressors and their anxiety at work and home. As predicted, the high-threat stressors were the most likely generate home-experienced anxiety, and work-experienced anxiety served as u key mediator. Implications relating to models of work and family well-being are discussed.